2014
DOI: 10.1128/jvi.01383-14
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Influenza A Virus RNA Polymerase Components and Retinoic Acid-Inducible Gene I

Abstract: The influenza A virus genome possesses eight negative-strand RNA segments in the form of viral ribonucleoprotein particles (vRNPs) in association with the three viral RNA polymerase subunits (PB2, PB1, and PA) and the nucleoprotein (NP). Through interactions with multiple host factors, the RNP subunits play vital roles in replication, host adaptation, interspecies transmission, and pathogenicity. In order to gain insight into the potential roles of RNP subunits in the modulation of the host's innate immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 81 publications
3
37
2
Order By: Relevance
“…However, the virus remains vulnerable during the transit to the nucleus, since at this stage of infection neither the classic IFN antagonist NS1 (Hale, 2014) nor the host response suppressors PA-X (Jagger et al, 2012) or PB1-F2 (Varga et al, 2011) would be expressed. Therefore, it appears plausible that the nucleocapsids themselfes have to cope with the pathogen recognition system, an assumption that is in agreement with our data and also with previous reports that FLUAV polymerase subunits can prevent IFN induction (Marcus et al, 2005; Perez-Cidoncha et al, 2014) and interact with RIG-I and MAVS (Graef et al, 2010; Iwai et al, 2010; Li et al, 2014; Liedmann et al, 2014). Moreover, for influenza B virus it was demonstrated that nucleocapsids were sufficient to induce IFN, whereas for FLUAV RNA synthesis was required (Osterlund et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…However, the virus remains vulnerable during the transit to the nucleus, since at this stage of infection neither the classic IFN antagonist NS1 (Hale, 2014) nor the host response suppressors PA-X (Jagger et al, 2012) or PB1-F2 (Varga et al, 2011) would be expressed. Therefore, it appears plausible that the nucleocapsids themselfes have to cope with the pathogen recognition system, an assumption that is in agreement with our data and also with previous reports that FLUAV polymerase subunits can prevent IFN induction (Marcus et al, 2005; Perez-Cidoncha et al, 2014) and interact with RIG-I and MAVS (Graef et al, 2010; Iwai et al, 2010; Li et al, 2014; Liedmann et al, 2014). Moreover, for influenza B virus it was demonstrated that nucleocapsids were sufficient to induce IFN, whereas for FLUAV RNA synthesis was required (Osterlund et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…This recognition might be coupled with viral transcription and replication that involve active viral polymerase and other host factors. This is of particular interest since RIG-I has been observed to partially relocalize into the cell nucleus during late stages of infection (62); however, whether this relocalization event correlates with IFN induction requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its structural role, NP also diminishes PRR activation by recruiting the cellular RNA helicases UAP56 and URH49, supposedly by unwinding any dsRNA that arises during genome replication (19). Moreover, two studies found that RNPs can interact with RIG-I or sequester it to the nucleus (22,23). PB1, PB2, and PA also interact with the host cell RNA polymerase II repressor DR1, which downregulates the expression of FLUAV-relevant ISGs, like RIG-I, MDA5, MX1, and IFITM (24).…”
Section: Rig-i Escape Mechanisms By Structural Components Of Fluavmentioning
confidence: 99%